Abdulla Qahhor and Storytelling (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
When discussing the genre of storytelling, one cannot overlook Abdullah Qahhor's narratives and his impact on Uzbek literature. This article examines Qahhor's contributions to Uzbek storytelling, explores the narrative genre's significance in Uzbek literature, and analyzes the destinies of the story's protagonists.